2009
DOI: 10.1515/bc.2009.040
|View full text |Cite
|
Sign up to set email alerts
|

Amidinoanthracyclines – a new group of potential anti-hepatitis C virus compounds

Abstract: Hepatitis C virus (HCV) infections represent one of the major and still unresolved health problems because current therapy is effective in only 50-80% of cases, depending on viral genotype. A large group of amidinoanthracyclines, with decreased acute toxicity and cardiotoxicity compared to the parent antibiotics, was tested in a high-throughput fluorometric HCV helicase assay. Here, we report the selection of more than 50 potent inhibitors of helicase activity that inhibit the enzyme with IC(50) values in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…There are only a few classes of helicase inhibitors that have been reported to slow HCV RNA replication in cell culture system of viral replication. HCV helicase inhibitors reported to act as antiviral include nucleoside mimics [29] triphenylmethanes [30], acridones [31], [32], amidinoanthracyclines [33], tropolones [34], symmetrical benzimidazoles [35][37] and primuline derivatives [38]. A very few studies have been reported targeting NS3 helicase by using flavonoid.…”
Section: Methodology and Principal Findingsmentioning
confidence: 99%
“…There are only a few classes of helicase inhibitors that have been reported to slow HCV RNA replication in cell culture system of viral replication. HCV helicase inhibitors reported to act as antiviral include nucleoside mimics [29] triphenylmethanes [30], acridones [31], [32], amidinoanthracyclines [33], tropolones [34], symmetrical benzimidazoles [35][37] and primuline derivatives [38]. A very few studies have been reported targeting NS3 helicase by using flavonoid.…”
Section: Methodology and Principal Findingsmentioning
confidence: 99%
“…Some anthracyclines, such as doxorubicin, daunomycin, epirubicin, and nogalamycin, as well as their derivatives, have been identified as NS3 helicase inhibitors [ 24 , 25 ]. Anthracyclines have a hydroxyanthraquinone moiety in their chemical structure, and mitoxantrone, which is also known to inhibit NS3 helicase, is an analogue of hydroxyanthraquinone [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, only a few classes of helicase inhibitors have been reported to slow HCV RNA replication in cells. HCV helicase inhibitors reported to act as antivirals include nucleoside mimics (13), triphenylmethanes (14), acridones (8,15), amidinoanthracyclines (16), tropolones (17), symmetrical benzimidazoles (18–20) and primuline derivatives (21). …”
Section: Introductionmentioning
confidence: 99%